PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BERBAGI PENGETAHUAN SECARA AKTIF TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 KOTO XI TARUSAN - Widya Ningsih, Yolian; Amadi Putra, Atus; Edriati, Sofia (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research is motivated by the students understanding of mathematical concepts are still low. This study aims to determine whether students understanding of concepts that implement various strategies to actively better knowledge of the students understanding of the concepts that apply to conventional teaching class VIII SMPN1 Tarusan academic year 2013/2014.This research is an experimental study of the subject with a random design. The population in this study were all students of class VIII SMPN1 Koto Tarusan listed in the Academic Year 2013/2014, with the sample is a class VIII.1 student as an experimental class and VIII. 2 as the control class. The instrument in this study is the final test in the form of an essay by using the concept of understanding and assessment indicators based analytic rubric, the reliability of the test is 0.886. data analysis techniques are used by one party t test with the help of MINITAB. Based on hypothesis testing using t-test of the party with the help of MINITAB, obtained P-value of 0.000 is smaller than α = 0.05. It can be concluded that the students understanding of mathematical concepts by applying various strategies to actively better knowledge than the students understanding of mathematical concepts by applying conventional learning model class VIII SMPN1 Koto XI Tarusan Academic Year 2013/2014 at the 95% confidence interval.